Effects of Medium Density Fiberboards (MDF) Recycling Methods on Fiber Dimensions and Some Reconstructed Board Properties - Olgun, Çagri; Ateş, Saim; Uzer, Emre (University of Zagreb, Faculty of Forestry and Wood Technology, 2023)
In this study, different methods, including acid hydrolysis (phosphoric and formic acid), thermohydrolysis, and microwave methods were tested for recycling of fiberboards made of 100 % beech and 70 % beech + 30 % pine wood fibers, which are widely sold in the market. The impacts of the using methods on the fibers were investigated with the help of a device that determines the fiber dimensions according to optical principles. In a laboratory setting, test boards were constructed using recycled fibers, and the changes in certain physical and mechanical qualities were studied. As a result, it was determined that recycled fibers obtained from microwave and thermo-hydrolysis fibers could be effectively used in fiberboard production. However, the proportion of fibers, longer than 1.24 mm, was decreased by about 30 % with the phosphoric acid method for MDF samples composed of 100 % beech fiber. The fiberboards could not be obtained from fibers recycled through acid hydrolysis except for phosphoric acid method with 100 % beech fibers.
Keywords: Forestry; otpadni MDF; recycling; SD1-669.5; svojstva ploče; board strenght; waste MDF; waste mdf; recikliranje; reciklirana vlakna; recycled fibers; fiber properties; svojstva vlakana; 12. Responsible consumption